Motion Control in Offshore and Dredging - Albers, P.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
Motion Control finds applications in many offshore, subsea and dredging installations. Motion Control is always based on a combination of mechanical-, electrical- and hydraulic drive systems together with control techniques. The book provides the basic theory of hydraulic controls, behaviour of hydraulic fluids, hydraulic component functions, parameter selections, calculation of basic hydraulic systems and basic theory of electrical drives: asynchronous motors with frequency drives. Apart from the theoretical background on the drive principles, many new practical applications are given on the design of drive and control techniques for the offshore and dredging industry, for example, the design of the saw that had to cut the nose from the Russian submarine "Kursk" before it could be salvaged from the seabed. Special attention is given to the static and dynamic behaviour of hydraulically and electrically driven systems, the behaviour of feedback control systems with the remaining dynamics and accuracies that can be obtained. Many examples are given of installed drives for offshore applications, pipe tensioners, pipe handling equipment, pipe-lay towers. Detailed information is presented on active and passive heave compensators for cranes, deep sea installations, access systems suction dredgers and the design of high pressure gas equipment in these systems.
Hydraulic energy converters -- Hydraulic energy control, conductive part -- Conductive part, piping and fluids -- Fluid conditioners and hydraulic accumulators -- AC induction machines -- Control technology -- Linear drives, open-loop -- Linear drives, closed loop systems -- Heave compensation -- Rotating drives -- Subsea drives -- Safety design rules -- Erratum to: Motion Control in Offshore and Dredging.
Keywords: Engineering; Vibration; Engineering design; System safety; Ocean engineering; Engineering; Vibration, Dynamical Systems, Control; Offshore Engineering; Engineering Design; Quality Control, Reliability, Safety and Risk